Safety of closed‐loop therapy during reduction or omission of meal boluses in adolescents with type 1 diabetes: a randomized clinical trial. Issue 11 (6th July 2014) - Elleri, D.; Maltoni, G.; Allen, J. M.; Nodale, M.; Kumareswaran, K.; Leelarathna, L.; Thabit, H.; Caldwell, K.; Wilinska, M. E.; Calhoun, P.; Kollman, C.; Dunger, D. B.; et al.
Abstract We evaluated the safety and efficacy of closed‐loop therapy with meal announcement during reduction and omission of meal insulin boluses in adolescents with type 1 diabetes (T1D). Twelve adolescents with T1D [six male; mean (s.d.) age 15.9 (1.8) years; mean (s.d.) glycated haemoglobin (HbA1c) 77 (27) mmol/mol] were studied in a randomized crossover study comparing closed‐loop therapy with meal announcement with conventional pump therapy over two 24‐h stays at a clinical research facility. Identical meals were given on both occasions. The evening meal insulin bolus was calculated to cover half of the carbohydrate content of the meal and no bolus was delivered for lunch. Plasma glucose levels were in the target range of 3.9–10 mmol/l for a median [interquartile range (IQR)] of 74 (55, 86)% of the time during closed‐loop therapy with meal announcement and for 62 (49, 75)% of the time during conventional therapy (p = 0.26). Median (IQR) time spent with plasma glucose levels > 10 mmol/l [23 (13, 39) vs. 27 (10, 50)%; p = 0.88] or < 3.9 mmol/l [1(0, 4) vs. 5 (1, 10)%; p = 0.24] and mean [standard deviation (SD)] glucose levels [8.0 (7.6, 9.3) vs. 7.7 (6.6, 10.1) mmol/l, p = 0.79] were also similar. In conclusion, these results assist home testing of closed‐loop delivery with meal announcement in adolescents with poorly controlled T1D who miscalculate or miss meal insulin boluses.